Предмет: Математика,
автор: ramzilyagaf
Помогите упростить выражение!
Приложения:
Ответы
Автор ответа:
0
(a√a+b√b)/(√a+√b)(a-b)+2√b/(√a+√b)-√(ab)/(a-b)=
=(a√a+b√b+2a√b-2b√b-a√b-b√a)/(√a+√b)(a-b)=
=(a√a+a√b-b√b-b√a)/(√a=√b)(a-b)=[a(√a+√b)-b(√a+√b)]/(√a+√b)(a-b)=
=(√a+√b)(a-b)/(√a+√b)(a-b)=1
=(a√a+b√b+2a√b-2b√b-a√b-b√a)/(√a+√b)(a-b)=
=(a√a+a√b-b√b-b√a)/(√a=√b)(a-b)=[a(√a+√b)-b(√a+√b)]/(√a+√b)(a-b)=
=(√a+√b)(a-b)/(√a+√b)(a-b)=1
Похожие вопросы
Предмет: История,
автор: komlevav01
Предмет: Русский язык,
автор: Аноним
Предмет: Английский язык,
автор: sofiagarbar5
Предмет: Информатика,
автор: irinka20022011
Предмет: Математика,
автор: ученикова3а